STRUGGLE AS SEEN IN JOHN STEINBECK’S THE PEARL - Tesalonika Gloria Wuisan; Noldy Pelenkahu; Ceisy N. Wuntu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This skripsi aims at revealing the struggle in John Steinback the pearl 1947 the analysis foceused on kino, as the main character in this novel. How far struggle is revealed is the objective of this research. This research applies objective theory of literature as the approach to analyze the data. Regarding the theory, the data are only from the word itself. This is not statistically analyzed for this is qualitative research it is found that, there are reasons of why kino should be in the effort of struggling About what he wants to It is understood that it is because he wants to save his son stung by a scorpion which are the sometimes he should be in an effort for his family’s financial difficulties and the society’s bad treatment to kino’s family that is considered as the society that belong to the lower class society’s. Everyone has difficulties in real life; the phenomenon is not exclusive to families. Everyone wants to live a naturally enjoyable life. They do this because they want a life free from trouble so they can enjoy it. However, the protagonist of The pearl book, Kino, a pearl diver, must struggle to overcome all of his personal problems. Humanly, all people want to have a happy life. It is because they want to have the free problems in life so that can enjoy the life